Childhood B-lymphoblastic leukemia: Integrating cytogenetics with other prognostic parameters and correlation with post-induction remission - Neelum Mansoor; Saba Jamal; Sidra Maqsood; Fatima Meraj; Mamona Mushtaq; Sadia Imran; Aamir Ehsan (Elsevier, 2023)
Background: Cytogenetics is irrefutably one of the most significant prognostic markers which have imparted ease and feasibility in the classification of acute leukemia. It is an essential prognostic tool in major treatment protocols for all hematological malignancies. This study aimed to note the frequency of different cytogenetic aberrations in children with B-ALL, their association with risk factors, and impact on post-induction remission status. Methods: A retrospective study was conducted in the Hematology department of The Indus Hospital, Karachi. All newly diagnosed patients of B-ALL (aged 1-17 years) from October 2, 2020 to October 13, 2021 were included. They were treated with modified Children's Oncology Group (COG) protocol. Cytogenetic studies including conventional karyotyping and fluorescence in situ hybridization (FISH) for BCR::ABL1, ETV6::RUNX1, and MLL gene rearrangement were performed on semi-automated cell imaging. Results: Among 238 patients, cytogenetic abnormalities were identified in 146 (61.3%) cases. A normal karyotype was observed in 92 (38.7%), high hyperdiploidy in 56 (24%), random structural abnormalities in 22 (9.2%), t (1:19) in 21 (8.8%), t (9; 22) in 12 (5.0%), complex karyotype in 10 (4.2%), 11q abnormalities in 5 (2.1%) and monosomy 7 in 1 (0.4%) case(s). FISH positivity for MLL, BCR::ABL1 and ETV6::RUNX1 was observed in 6 (2.5%), 18 (7.5%), and 20 (8.4%), cases, respectively. Post induction morphological remission was observed in 98.3% of cases. Conclusion: The overall frequency of cytogenetic abnormalities in the current cohort is comparable to previously reported studies. Our data also suggest the value of combining the karyotype and FISH techniques to increase the likelihood of detection of recurrent cytogenetic abnormalities. Even though there was a lack of correlation between genetic abnormalities and early outcome, a follow-up may be useful to ascertain the correlation with long-term survival.